KETAHANAN PANGAN RUMAH TANGGA PETANI KOPI DI KABUPATEN LAMPUNG BARAT - Meilia Anggraini; Wan Abbas Zakaria; Fembriarti Erry Prasmatiwi (Lampung University, 2014)
The research goals were to discover the level of food security and the factors that influenced the level of household food security of coffee farmers in West Lampung Regency. The research was conducted at Sekincau and Way Tenong Sub district for those sub districts are centers of coffee production and food-prone subdistricts in West Lampung Regency. By equal consideration, from each district were selected 2 villages: villages of Giham Sukamaju and Sekincau in Sekincau Subdistrict, while for Way tenong Subdistrict was selected villages of Tanjung Raya and Mutar Alam. The research used household survey in 53 coffee farmers who were chosen by simple random sampling. Cross-classification between expenditures and the share of household energy adequacy level developed was used to answer the first goal. Ordinal logistic model was used to answer the second goal. The results showed that the coffee farmer households who achieved the level of food security as withstand was 15.09%, as less was 11.32%, as vulnerable was 62.26%, and the level of food insecurity was 11.32%. Based on the test results obtained by ordinal logistic, the household food security was positively affected by household income and negatively by the price of rice. Key words: coffee, energy sufficiency, food security, household, ordinal logistic